(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
Neurolinguistics, as an interdisciplinary field, investigates the neural mechanisms underlying human language processing, acquisition, and disorders. This article provides a descriptive analysis of the integrative relationship between neurolinguistics and other scientific disciplines, including linguistics, psychology, neuroscience, and cognitive science. The primary aim of this study is to elucidate how these interdisciplinary connections contribute to a comprehensive understanding of language functions in the brain, particularly within the context of Uzbek and Turkic language speakers. The methodological approach is based on a systematic review of existing theoretical frameworks and empirical studies, focusing on the synthesis of findings from neuroimaging, electrophysiology, and clinical observations. Key results indicate that the integration of neurolinguistic data with psycholinguistic models and neurobiological principles significantly enhances the explanatory power regarding language lateralization, bilingualism effects, and aphasia recovery patterns. Furthermore, the study highlights the importance of considering language-specific structural and typological features, such as agglutinative morphology, in neurolinguistic research. The findings suggest that a multidisciplinary approach is essential for advancing theoretical models and practical applications in language rehabilitation and education. These abstract underscores the necessity of continued interdisciplinary collaboration to address complex questions about the neural basis of language.